Multi-Level Detachment Deformation of the West Segment of the South Dabashan Fold-and-Thrust Belt, South China: Insights From Seismic-Reflection Profiling - Huang, Hanyu; Mei, Qinghua; He, Dengfa; Lu, Renqi; Li, Yingqiang (Frontiers in Earth Science, 2021)
The South Dabashan arcuate tectonic belt located at the northern margin of the Yangtze Block in South China, which primarily comprises a series of northwestern (NW)-trending foreland fold-and-thrust belts (FTBs), is useful for determining the intracontinental orogeny processes of the Yangtze Block. In this study, we integrated the latest pre-stack depth migration of three- and two-dimensional seismic profiles, drill hole, and outcrop data to explore the structural geometric and kinematic features of the west segment of the South Dabashan FTB. This belt is characterized by multi-level detachment structures due to the presence of three predominant sets of weak layers: the Lower Triassic Jialingjiang Formation gypsum interval, Silurian mudstone beds, and Cambrian shale beds. The belt is accordingly subdivided vertically into three structural deformation systems. The upper system appears above the Jialingjiang Formation gypsum layer and exhibits Jura-type folds, which were formed by alternating anticlines and synclines that are parallel to each other. The middle system comprises Silurian shale as the base and Jialingjiang Formation gypsum interval as the passive roof and exhibits NW-striking imbricate thrusts. The lower system is bounded by Cambrian and Silurian detachment layers, forming a duplex structure. The Sinian and Proterozoic basements below the Cambrian were not involved in deformation. The west segment of the South Dabashan FTB underwent four periods of tectonic evolution: Late Jurassic to Early Cretaceous, Late Cretaceous, Paleogene, and Neogene to Quaternary. The deformation was propagated southward in imbricate style, resulting in the passive uplifting of the overlying strata. Based on the magnetotelluric and deep seismic profile, the tectonic processes of the west segment of the South Dabashan FTB are inferred to be primarily controlled by the Yangtze Block northward subduction under the Qinling Orogenic Belt and the pro-wedge multi-level thrusting during the Late Jurassic to Cretaceous.